IMPLEMENTASI KEBIJAKAN DANA DESA RONDINGO KECAMATAN KINOVARO KABUPATEN SIGI - Mini Mini; Juemi Juemi (Kampus Akademik Publiser, 2023)
Implementation of fund policy in Rondingo Village, Kinovaro District, Sigi Regency uses qualitative descriptive research using policy theory from Edward III with four aspects, namely communication, resources, disposition and bureaucratic structure. In this research, the author used a purposive sampling technique in selecting informants, namely by selecting people who were considered to understand the problem being studied. Based on the research results, it shows that the implementation of village fund policies in Rondingo village is less effective, where three of the four aspects of the policy are poorly implemented, namely communication, resources and bureaucratic structure, while the disposition aspect is good. Based on the research results, it shows that the process of socializing the village fund policy carried out by Rondingo village officials only involved a small portion of the community, so that there are still many people in Rondingo village who do not understand the direction and objectives of a village fund policy. Furthermore, the unequal level of education of Rondingo Village officials affects their abilities and skills in implementing village fund policy programs. Lastly, there is a lack of supervision of the responsibilities of Rondingo village officials in carrying out their duties and functions optimally. This research shows that only the disposition aspect is included in the good category.